A review of Forensic Entomology literature in the Northeastern United States. Issue 5 (12th August 2021) - Weidner, Lauren M.; Hans, Krystal R.
ABSTRACT: A comprehensive review of forensic entomology literature in the northeastern portion of the United States was conducted searching the earliest possible publication date through early 2020. Thirteen states and the capital were included in this region and yielded 172 publications. As a region, the main areas of the publications were arrival and decomposition, myiasis, and papers yielding information pertaining to biodiversity. However, there was a large fluctuation in total publications by state with Maryland producing over 30 publications, and Delaware and Vermont each producing one. Within this region only 15 publications from seven states were found concerning development, showing a severe deficiency in this category. Additional work is needed in this geographic area of the United States in most categories of work related to forensic entomology research. This article is categorized under: Forensic Biology > Interpretation of Biological Evidence Forensic Anthropology > Time Since Death Estimation Crime Scene Investigation > Crime Scene Examination Abstract : Piglet decomposition displaying multiple life stages and orders of insects (photo credit: Lauren M. Weidner).